2019
DOI: 10.1016/j.adro.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Performance Status and Comorbidity on Palliative Radiation Treatment Tolerance and End-Of-Life Decision-Making

Abstract: PurposePrevious studies have indicated a relationship between functional status and comorbidity on overall survival when treating patients with bone and brain metastases. However, the degree to which these findings have been integrated into modern-day practice remains unknown. This study examines the impact of performance measures, including Karnofsky Performance Status (KPS) and comorbidity, on palliative radiation therapy treatment tolerance and fractionation schedule. The relationship between a shorter frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Maebayashi et al reported a rate of 2.9% premature discontinuation among 2141 patients who underwent RT at their institution, which was most commonly due to deterioration of performance status (60% of discontinuations) 12 . In another single‐institution study examining the impact of clinical factors on palliative RT treatment tolerance and fractionation schedule, Perlow et al found that lower Karnofsky Performance Scale (KPS) score and high comorbidity were predictive of increased frequency of major RT treatment interruption 13 . In our analysis, we similarly found that patients with premature RT termination were more likely to have a higher comorbidity CCI score, though this was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Maebayashi et al reported a rate of 2.9% premature discontinuation among 2141 patients who underwent RT at their institution, which was most commonly due to deterioration of performance status (60% of discontinuations) 12 . In another single‐institution study examining the impact of clinical factors on palliative RT treatment tolerance and fractionation schedule, Perlow et al found that lower Karnofsky Performance Scale (KPS) score and high comorbidity were predictive of increased frequency of major RT treatment interruption 13 . In our analysis, we similarly found that patients with premature RT termination were more likely to have a higher comorbidity CCI score, though this was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%